2017
DOI: 10.23917/warta.v19i2.2742
|View full text |Cite
|
Sign up to set email alerts
|

PEMANFAATAN DAUN SALAM (Eugenia polyantha) SEBAGAI OBAT HERBAL DAN REMPAH PENYEDAP MAKANAN

Abstract: Eugenia polyantha, one of Indonesian medicine plant, often used insociety as traditional medicine and also Indonesian culinary additives.Daun salam is called Indonesian bay-leaf, the leaves contain only tiny amounts of an essential oil 0.2%. As main components, eugenol, methylchavicol, and citral have been identified. Thus application to usedof Eugenia polyantha have done. The aim of the present work was the application of Eugenia polyantha for food and health in the community area of Keraton Surakarta. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
20

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 0 publications
0
14
0
20
Order By: Relevance
“…Liliwirianis et al found Salam leaf contained polyphenol compounds such as flavonoid and tannin [15]. Harismah and Chusniatun stated that flavonoid had anti-inflammatory, antiplatelet, anticholesterol, antidiabetes, and antioxidant effect that could be benefit to human [16]. Prahstuti et al found that quercetin and phloretin were the most types of flavonoids contained in Salam leaf [17].…”
Section: Figure 1: Photomacrography Of Heart Muscle On Negative (A) Amentioning
confidence: 99%
“…Liliwirianis et al found Salam leaf contained polyphenol compounds such as flavonoid and tannin [15]. Harismah and Chusniatun stated that flavonoid had anti-inflammatory, antiplatelet, anticholesterol, antidiabetes, and antioxidant effect that could be benefit to human [16]. Prahstuti et al found that quercetin and phloretin were the most types of flavonoids contained in Salam leaf [17].…”
Section: Figure 1: Photomacrography Of Heart Muscle On Negative (A) Amentioning
confidence: 99%
“…Rimpang lengkuas ini tidak hanya dimanfaatkan masyarakat sebagi rempah-rempah namun juga dijadikan sebagai obat tradisonal [57][58] [59] . Hal ini didukung dengan berbagai penelitian yang menguatkan bahwa rebusan rimpang lengkuas dapat dijadikan sebagai obat tradisional [60][61] [62] . Banyak para peneliti yang mendukung bahwa rebusan rimpang lengkuas dapat dijadikan sebagi obat tradisional [63][64] [65] .…”
Section: Pendahuluanunclassified
“…ekstrak jinten hitam memiliki senyawa identitas yaitu luteolin, sedangkan ekstrak daun salam adalah flouretin. Perbedaaan potensi penurunan kadar asam urat terjadi karena perbedaan senyawa aktif tersebut sehingga dari hasil yang diperoleh senyawa flueoretin lebih poten dari ekstrak daun salam (Harsimah & Chusniatun, 2016).…”
Section: Metode Penelitianunclassified